Vegetation Analysis of the Tagafura Protected Forest in the City of Tidore Islands - Sabaria Niapele; Tamrin Salim (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The existence of Forest park vegetation in Tagafura as the  vegetation cover are  important to be maintain and preserved, since it’s effective for the human live on the earth. The function of this forest park  is to defend the field around the forest in several ways such as, the water cycle, avoid the flood, erosion scheming and the soil fruitfulness keeper. The Tagafura Forest Park has a lot of natural resource, but the structure and the composition of the field are not completely found yet. Based on the the statement above the Researcher are interested to conduct the research entitled “ VEGETATION ANALYSIS OF THE TAGAFURA FOREST PARK IN TIDORE ISLAND to know about the structure and the composition of the vegetation in the Forest park of Tagafura and be able to being as the government substance while made a decision about the Forest park. This research used purposive sampling with a combination of to track and double plot to placement the plot. The data then analyzing used the density and relative density formula, domination and relative domination formula, frequency and relative frequency formula and The Importance Value Index (INP). Based on the research result, the data was founded that the forest has 25 structures include 15 types of Seedlings, 10 type of Stakes, 13 type of poles and 12 types of tress.  The domination of the composition type amount the growth based on the INP is (1). Augenia aromatic with the INP in Seedling are 45,49. INP for Stand  are 18,05. INP for the  are 23,67 and the INP for the trees are 132.08. (2). Myristica fragrans has the INP for the seedlings are 31.44. INP for Stand are 15.11. INP for the poles are 30.27  and the INP for the trees are 47.25.  (3). Gnetum gnemo has the INP for the seedlings are 19,48. INP for Stand are 24.21. INP for the  poles are 49.92  and the INP for the trees are 10.83. (4). Arenga Pinnata has the INP for the seedlings are 18,13. INP for Stand are 36.11. INP for the  poles are 24.04  and the INP for the trees are 17.51. (5). Cinnamomum verum has the INP for the seedlings are 11.84. INP for Stand are 33.17. INP for the  poles are 26.42  and the INP for the trees are 7.36.